Analysis of efficiency droop in 280-nm AlGaN multiple-quantum-well light-emitting diodes based on carrier rate equation. (22nd January 2015) - Yun, Joosun; Shim, Jong-In; Hirayama, Hideki
Abstract: The efficiency droop in 280-nm AlGaN multiple-quantum-well (MQW) ultraviolet (UV) light-emitting diodes (LEDs) is analyzed using the carrier rate equation. It is shown that the internal quantum efficiency (ηIQE ), injection efficiency (ηinj ), light-extraction efficiency (ηLEE ), Shockley–Read–Hall recombination coefficient ( A ), and Auger coefficient ( C ) can be determined by the carrier rate equation using the theoretical radiative recombination coefficient ( B ), experimentally measured wavelength spectrum, and external quantum efficiency (ηEQE ). The results show that the carrier spillover from the MQWs to the p-AlGaN layer is the main cause of the efficiency droop.